Immunophenotyping of Sheep Paraffin-Embedded Peripheral Lymph Nodes - Melzi, Eleonora; Rocchi, Mara S.; Entrican, Gary; Caporale, Marco; Palmarini, Massimo (Frontiers in Immunology, 2018)
Sheep are not only a major livestock species globally, they are also an important large animal model for biomedical research and have contributed to our understanding of the ontogeny and architecture of the mammalian immune system. In this study, we applied immunohistochemistry and multicolor immunofluorescence in fixed and paraffin-embedded lymph nodes to phenotype the key populations of antigen presenting cells, lymphocytes and stromal cells that orchestrate the host adaptive immune response. We used an extensive panel of antibodies directed against markers associated with dendritic cells (MHC class II, CD83 and CD208), macrophages (CD11b, CD163 and CD169), stromal cells (CNA.42, S100 and CD83), and lymphocytes (CD3, Pax5, CD4, CD8). Using different methods of tissue fixation and antigen retrieval, we provide a detailed immunophenotyping of sheep lymph nodes including the identification of potential subpopulations of antigen presenting cells and stromal cells. By characterizing cells expressing combinations of these markers in the context of their morphology and location within the lymph node architecture, we provide valuable new tools to investigate the structure, activation and regulation of the sheep immune system in health and disease.